تأثير برنامج تدريبي بالأثقال باستخدام Repetition Maximal (RM) لتحسين القوة العضلية لدى لاعب كرة القدم (تحت 20 سنة) - مديقش , مروان عبد العزيز احمد (Scientific Journal of University of Benghazi, 2023)
The research aims to design a weight training program by using the maximum force of each player under the age of 20 years old the category of young people in Al-Hilal club (Benghazi). The researcher used the trial approach for one group that fits the research goals. The research sample was chosen according to the intential method, it included (20 players) who had participated in (Under-20) Libyan football league .The training program lasted for (10 weeks) ,(4) units a week. It was done within the special prepration andcompetitions duration . The researcher used the special measurments of weight training such as: Board jump – Back strenghth dynamometer –Spinal flixbility –Throwing the medical ball (2 kgs). The results of the weight training program by using the (RM) were very good and the weight training has a positive impact on the players. The most importnant recommendations were to considerindividual differences among players when they use weights in training by using (RM), in addation pushing every player’s limit to control the intensity during the training session.